Perspectives for Ag2S NIR-II nanoparticles in biomedicine: from imaging to multifunctionality. Issue 41 (27th September 2019) - Shen, Yingli; Lifante, José; Ximendes, Erving; Santos, Harrison D. A.; Ruiz, Diego; Juárez, Beatriz H.; Zabala Gutiérrez, Irene; Torres Vera, Vivian; Rubio Retama, Jorge; Martín Rodríguez, Emma; Ortgies, Dirk H.; Jaque, Daniel; et al.
Abstract : A critical analysis of the synthesis routes, properties and optical features of Ag2 S nanoparticles is presented. The future perspectives of this material for advanced bioimaging are discussed. Abstract : Research on near-infrared (NIR) bioimaging has progressed very quickly in the past few years, as fluorescence imaging is reaching a credible implementation as a preclinical technique. The applications of NIR bioimaging in theranostics have contributed to its increasing impact. This has brought about the development of novel technologies and, simultaneously, of new contrast agents capable of acting as efficient NIR optical probes. Among these probes, Ag2 S nanoparticles (NPs) have attracted increasing attention due to their temperature-sensitive NIR-II emission, which can be exploited for deep-tissue imaging and thermometry, and their heat delivery capabilities. This multifunctionality makes Ag2 S NPs ideal candidates for theranostics. This review presents a critical analysis of the synthesis routes, properties and optical features of Ag2 S NPs. We also discuss the latest and most remarkable achievements enabled by these NPs in preclinical imaging and theranostics, together with a critical assessment of their potential to face forthcoming challenges in biomedicine.